2003
DOI: 10.1024/0300-9831.73.5.351
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Vitamin E in Cadmium-Induced Oxidative Damage in Rabbit’s Blood, Liver and Kidneys

Abstract: The aim of this work was to determine the effect of dietary vitamin E intake on lipid peroxidation (LPO) by measuring thiobarbituric acid reactive substances (TBARS), vitamin E and reduced glutathione (GSH) levels, and glutathione peroxidase (GSH-Px: EC 1.11.1.9) activity in plasma, red blood cells (RBC), livers, and kidneys of rabbits dosed with cadmium (Cd). Six-month-old clinically healthy New Zealand White rabbits (8 in each group) were given tap water only, containing 1 g CdCl2/L, or tap water with CdCl2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
3
13
1
Order By: Relevance
“…In another study, "Turguta et al (29) " reported that administration of the antioxidant agent Vitamin E together with metal resulted in the recovery of malondialdehyde. "Beytut et al (30) " and "Ognjanovic et al (31) " demonstrated reduction in increased lipid peroxidation due to heavy metal toxicity by Vitamin E."Moneim et al (28) " found that synchronous treatment of flaxseed oil with lead acetate caused increase in the level of malondialdehyde, which is in contrast with above findings. We also assessed antioxidant enzyme, glutathione reductase (GR) at the end of two months in testicular tissue of animals of different groups and found that the level of this enzyme was decreased in lead nitrate treated group in comparison to control group because of persistent oxidative stress.…”
Section: Discussioncontrasting
confidence: 51%
“…In another study, "Turguta et al (29) " reported that administration of the antioxidant agent Vitamin E together with metal resulted in the recovery of malondialdehyde. "Beytut et al (30) " and "Ognjanovic et al (31) " demonstrated reduction in increased lipid peroxidation due to heavy metal toxicity by Vitamin E."Moneim et al (28) " found that synchronous treatment of flaxseed oil with lead acetate caused increase in the level of malondialdehyde, which is in contrast with above findings. We also assessed antioxidant enzyme, glutathione reductase (GR) at the end of two months in testicular tissue of animals of different groups and found that the level of this enzyme was decreased in lead nitrate treated group in comparison to control group because of persistent oxidative stress.…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast, Sarkar et al (6) indicated that the RBC SOD and CAT activities decreased significantly with Cd and the pretreatment with vit E and/or selenium prior to Cd administration partially reversed these changes. In addition, Beytut et al (40) observed that the Cd treatment decreased the GSH-Px activity of RBC. Armutcu et al (41) demonstrated that plasma iron levels were significantly increased in the acetonetreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they concluded that vitamin E pretreatment incompletely lessens Pb-induced oxidative stress by changing antioxidant enzymes. [66] and [67] established the efficiency of vitamin E in decreasing oxidative stress in Cd -treated animals and proposed that declines in increased lipid peroxidation due to Cd poisonousness may be an significant factor in the action of vitamin E. [68] presented that the exposure to Cd produced marked elevation in the level of lipid peroxidation and a decline in SOD, glutathione peroxidase (GSH-Px) and CAT activities complemented by an upsurge in the rate of hemoglobin autoxidation in Swiss albino rats. Moreover, they verified that the cure with vitamin E significantly reduced the alterations caused by Cd exposure in all examined parameters.…”
mentioning
confidence: 99%
“…It is well-known to have been confirmed beneficial in certain disease courses. Because of the health problems induced by many environmental pollutants, much effort has been expended in evaluating the relative antioxidant potency of vitamin E [11][12][13][14]. Till the first decade of the twenty-one century, there is no information regarding the effect of vitamin E on the testicular toxicities induced by a mixture of heavy metals (Pb, Hg, Cd and Cu) exposure in mice or other mammals [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation